Pengaruh Loneliness Di Tempat Kerja Serta Peran Perceived Organization Support Dan Resilience Terhadap Psychological Well-Being Di Jabodetabek - Pramadhani, Nurisqia Caesar (UI Scholars Hub, 2024)
This study explores the impact of workplace loneliness on the psychological well-being of Generation Z and Millennial employees in the Greater Jakarta area, considering the role of perceived organisational support and resilience as moderating variables. Using a cross-sectional survey approach with 334 respondents, this study found that loneliness at work negatively affects psychological well-being. In contrast, POS and resilience have a significant positive influence. Resilience was also shown to moderate the relationship between workplace loneliness and psychological well-being, strengthening individuals' ability to deal with loneliness constructively. These results emphasise the importance of developing organisational policies that support employees' social connectedness and resilience to improve psychological well-being and productivity.